The Influence of the Bentonite Clay Coated Winter Wheat Seeds on Laboratory Germination (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, the influence of the norm of coating seeds of winter wheat with bentonite clay, the energy of seed germination, fertility, the length of caleoptiles, the length and number of roots on the laboratory condition were determined and the results were analyzed at the Southern Research Institute "Plant Physiology and Biochemistry"